Explorer : the mystery boxes : seven graphic stories - Roman, Dave; Telgemeier, Raina; Caffoe, Jason; Sechrist, Rad; Livingston, Stuart; Ramirez, Stephanie; Matte, Johane, 1971-; Phanekham, Saymone; Kibuishi, Kazu, 1978-; Carroll, Emily (New York : Amulet Books, 2012)
An anthology of short graphic works on the theme of a mysterious box and the marvels, or mayhem, inside
Under the floorboards / Emily Carroll -- Spring cleaning / Dave Roman and Raina Telgemeier -- The keeper's treasure / Jason Caffoe -- The butter thief / Rad Sechrist -- The soldier's daughter / Stuart Livingston with Stephanie Ramirez -- Whatzit / Johane Matte with Saymone Phanekham -- The escape option / Kazu Kibuishi
Keywords: Boxes -- Comic books, strips, etc. -- Juvenile fiction; Children's stories, American; Graphic novels; Short stories